Networks of Agricultural Innovation, A Way of Productive and Sustainable Development in Cuba - Zorio González, Elianys de la C.; Martínez Massip, Annia (Agrisost ISSN 1025-0247, 2019)
Context: The networks of agricultural innovation ensure the development of any society. They contribute to food safety and sustainable development of a country’s agriculture. However, in Cuba, sociological research is still insufficient in that sense. Aim: To analyze the networks of agricultural innovation among grain farmers in the municipality of Yaguajay, province of Sancti Spíritus. Methods: The analysis of social networks (SNA), based on a methodological convergence of qualitative and quantitative aspects, including observation, interviews, surveys, and the utilization of software UCINET to visualize the relationships. Following directed screening, 28 grain farmer-innovators in the municipality of Yaguajay were selected by triangulation of information collected from several institutions, and criteria for intentionality. Results: Inequalities were observed in the networks of agricultural innovation, since no women or youngsters were part of them. The networks also were discriminatory in terms of age and territoriality. Conclusions: The networks of agricultural innovation in grain production show a low degree of female and youth centrality. The innovation level is scanty due to the weak culture of innovation in institutional and farmer criteria. The networks are barely thick, with few links among farmers, little diffusion of innovation, and lack of effective and extended networks. In that sense, the connectivity of agricultural innovation networks is weak, thus limiting the development and sustainability of agricultural productivity.